Descrição arquivística em ambiente digital: proposta para aplicação do software ICA-AToM na coleção fotográfica em chapas de vidro do Museu Paraense Emílio Goeldi - NOBRE, Amanda Serrão (2017)
The aim is to present a proposal for archival description in a digital environment through the ICA-AtoM platform in the glass plate photographic collection of the Museu Paraense Emílio Goeldi (MPEG), to comprise and study the collection. The objective of this study was to record and analyze the effects of the use of ICA-AToM in the organization and access of the MPEG photographic archive. A bibliographic survey was made based on theses, articles and monographs related to Archives, photography and the ICA-AtoM application study in order to contextualize the photograph as a technique, testimony and archival document, followed by the proceedings to adopt for the description in this research and its insertions in a digital environment. As methodological procedures, was adopted a documentary analysis of the object of research to the photographs, with questionnaires and internal MPEG material (history and structure of the Institution) in the Guilherme de La Penha Archive. In order to respond through a case study, how is and how is the treatment of photographs in the archive environment and its access and diffusion in the digital environment.